2020
DOI: 10.1002/jssc.202000746
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of balms taken from Egyptian human mummies using solid‐phase extraction and gas chromatography–mass spectrometry

Abstract: The aim of this paper is to establish a protocol by solid‐phase extraction–gas chromatography–mass spectrometry leading to a wide and fine qualitative chemical characterization of the several natural substances present in human mummies’ balms, using a minimal quantity of samples. In this study, nine samples were analyzed from mummies dating back from the Third Intermediate Period to the Roman Period, and were provided by the Confluences Museum (Lyon, France). Using solid‐phase extraction, three fractions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Namely, in this study no hydrocarbon diagnostic biomarkers characteristic for bitumen were observed. The absence of diagnostic markers such as steranes and hopanes was confirmed in all chromatograms obtained by complementary experiments using Solid-Phase Extraction protocol (Mezzatesta et al, 2020b). This SPE protocol was performed on all of the samples and it permitted to clearly confirm the occurrence or the absence of bitumen in the studied archaeological samples.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Namely, in this study no hydrocarbon diagnostic biomarkers characteristic for bitumen were observed. The absence of diagnostic markers such as steranes and hopanes was confirmed in all chromatograms obtained by complementary experiments using Solid-Phase Extraction protocol (Mezzatesta et al, 2020b). This SPE protocol was performed on all of the samples and it permitted to clearly confirm the occurrence or the absence of bitumen in the studied archaeological samples.…”
Section: Discussionmentioning
confidence: 68%
“…After trimethylsilylation with, fractions 1 and 2 were solubilized with 60 μL of a hexane/DCM mixture (2/1; v/v) while fraction 3 was solubilized with 1.5 mL of hexane/DCM (2/1; v/v). The three fractions were then filtered on a PTFE cartridge (0.45 μm) before respective injections in GC-MS apparatus (Mezzatesta et al, 2020b).…”
Section: Saponificationmentioning
confidence: 99%
“…This work highlighted various substances present in mummification balms. PAHs are the only compounds that do not correspond to a natural substance but which have an anthropic origin [33]. Mummy balms containing PAHs appeared apart, and were highlighted by SIMPLISMA.…”
Section: Discussionmentioning
confidence: 99%
“…The organic phase was recovered and dried with anhydrous sodium sulfate, then filtered on filter paper. The solution was evaporated to dryness under a stream of nitrogen, trimethylsilylated and injected in GC-MS [33].…”
Section: Saponificationmentioning
confidence: 99%
“…After trimethylsilylation, fractions 1 and 2 were solubilized with 60 μL of a hexane/DCM mixture (2/1; v/v ), while fraction 3 was solubilized with 1.5 mL of hexane/DCM (2/1; v/v ). The three fractions were then filtered on a PTFE cartridge (0.45 μm) before respective injections in GC–MS apparatus [ 46 ].…”
Section: Methodsmentioning
confidence: 99%